دور الضبط القانوني والرقابة في ترشيد النفقات العمومية - بن علي, أمال; مسعودي, زكرياء (University of Eloued جامعة الوادي, 2021)
تهدف هذه الدراسة إلى التعرف على مفهوم ترشيد النفقات العمومية وعوامل نجاحها وفعاليتها على وجه الخصوص الصفقات العمومية باعتبارها نفقة من نفقات الدولة العمومية، فحماية المال العام من الفساد الذي تسببه الصفقات المشبوهة هو أحد أولى التدابير الواجب اتخاذها إذا ما أرادت الدولة الوصول إلى المحافظة عليه. كما تطرقت الدراسة لمفهوم الصفقات العمومية وإجراءات تنفيذها إضافة إلى تفعيل الرقابة على الصفقات العمومية كضابط مهم في ترشید الإنفاق العام التي تخضع له وجوبا بصورة واسعة بهدف مطابقة الصفقة للأهداف المتوخاة من وراء إبرامها ومطابقتها للقوانين والأنظمة المعمول بها. حيت خلصت هذه الدراسة أنه في غياب الضبط القانوني والرقابة الصارمة ينفتح باب الإستغلال السيء والاختلاس والتبديد على مصرعيه، لذى وجب على المشرع تدارك هذه الثغرات، وذلك من خلال تفعيل الرقابة في إطار ما يسمى بترشيد الإنقاق العام بما فيها نفقات الصفقات العمومية. The purpose of this study is to identify the concept of rationalization of public expenditure and its factors of success and effectiveness, in particular public transactions as an expense from public expenditure. Protecting public money from corruption caused by suspicious transactions is one of the first measures that must be taken if the state wants to reach it. The study also touched on the concept of public transaction and the procedures o their implementation, as well as activating the control of public transactions as an important officer in rationalizing the public expenditure, which is subject to a wide demand, with the aim of matching the transaction to the objectives of its conclusion and compliance with applicable laws and regulations. This study concluded that in the absence of legal control and strict supervision, the door of misuse, embezzlement and waste is opened to the
The role of legal control and control in rationalizing public
مقال
Keywords: ترشيد النفقات العمومية -الصفقات العمومية- قانون( 15-247)- ضابط الرقابة-المال العام; Rationalization of Public Expenditures; P ublic Transaction